Mapping of metabolic heterogeneity of glioma using mr‐spectroscopy - Franco, Pamela; Huebschle, Irene; Simon‐gabriel, Carl Philipp; Dacca, Karam; Schnell, Oliver; Beck, Juergen; Mast, Hansjoerg; Urbach, Horst; Wuertemberger, Urs; Prinz, Marco; Hosp, Jonas A.; Delev, Daniel; et al. (Cancers, 2021)
Proton magnetic resonance spectroscopy (1H‐MRS) delivers information about the noninvasive metabolic landscape of brain pathologies.1H‐MRS is used in clinical setting in addition to MRI for diagnostic, prognostic and treatment response assessments, but the use of this radiological tool is not entirely widespread. The importance of developing automated analysis tools for1H‐MRS lies in the possibility of a straightforward application and simplified interpretation of metabolic and genetic data that allow for incorporation into the daily practice of a broad audience. Here, we report a prospective clinical imaging trial (DRKS00019855) which aimed to develop a novel MR‐spectroscopy‐based algorithm for in‐depth characterization of brain lesions and prediction of molecular traits. Dimensional reduction of metabolic profiles demonstrated distinct patterns throughout pathologies. We combined a deep autoencoder and multi‐layer linear discriminant models for voxelwise prediction of the molecular profile based on MRS imaging. Molecular subtypes were predicted by an overall accuracy of 91.2% using a classifier score. Our study indicates a first step into combining the metabolic and molecular traits of lesions for advancing the preoperative diagnostic workup of brain tumors and improve personalized tumor treatment.
CRIS-Team Scopus Importer:2023-09-13
Keywords: 1H‐MRS; Chemical shift imaging; Glioma; Magnetic resonance spectroscopy; MR spectroscopy; MRS; Neurooncology; Neuroradiology; Neurosurgery; Radiomics